The university in ruins - Readings, Bill 1960-1994 (Harvard Univ. Press, 1996)
It is no longer clear what role the University plays in society. The structure of the contemporary University is changing rapidly, and we have yet to understand what precisely these changes will mean. Is a new age dawning for the University, the renaissance of higher education under way? Or is the University in the twilight of its social function, the demise of higher education fast approaching